Pengaruh Promosi Gratis Ongkir Shopee terhadap Loyalitas Mahasiswa Program Studi Manajemen Fakultas Ekonomi Universitas Batanghari - Laras Sati (Universitas Batanghari Jambi, 2021)
The reason researchers chose free shipping from Shopee is because Shopee offers quite profitable promotions, especially for students who like to shop online, in addition Shopee is ranked number one in e-commerce applications. This study aims to determine the Promotion of Shopee Management Loyalty Study Program Free and Student Loyalty Faculty of Economics Batanghari University and secondly to determine the effect of Free Shopee Delivery Promotion on Student Loyalty in Management Study Program, Faculty of Economics, Batanghari University. The research methodology used is quantitative method. The population in this study was students of management study program at the Faculty of Economics, Batanghari University, who are consumers / users of Shopee with a total sample of 73 people. Simple regression analysis, correlation test, determination coefficient and pt t. test. Shopee Internasional Indonesia is a company engaged in the sale of products online. Shopee free shipping promotion variables with an average score of 295,7 are included in the good criteria. Student loyalty variables with an average score of 303,3 are included in the good criteria. The regression equation value is Y = 0.677 + 0.803X + e. The correlation coefficient value is 0.652. the coefficient of determination (R2) is 0.426. Test t sig. <α (0.000 <0.05). Shopee is expected to always pay attention to the media used in making promotional offers and more convincing consumers / customers to take shopping actions.